Odpowiedź :
Odpowiedź:
√3 x²-9x+6√3≤0
a=√3 b=-9 c= 6√3
Δ=b²-4ac= 81-4√3*6√3= 81- 72=9 √Δ=3
x1=( -b-√Δ)/2a=( 9-3)/2√3= 3√3/3=√3
x2=(-b+√Δ)/2a=( 9+3)/2√3= 6√3/3=2√3
x∈<√3;2√3>
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]\huge\boxed{x\in\left<\sqrt3;\ 2\sqrt3\right >}[/tex]
Szczegółowe wyjaśnienie:
[tex]x(x\sqrt3-9)\leq-6\sqrt3\qquad|+6\sqrt3\\\\x^2\sqrt3-9x+6\sqrt3\leq0\qquad|\cdot\sqrt3\\\\3x^2-9x\sqrt3+18\leq0\qquad|:3\\\\x^2-3x\sqrt3+6\leq0\\\\a=1;\ b=-3\sqrt3;\ c=6\\\\\Delta=b^2-4ac\\\\\Delta=(-3\sqrt3)^2-4\cdot1\cdot6=27-24=3\\\\\sqrt\Delta=\sqrt3\\\\x_1=\dfrac{3\sqrt3-\sqrt3}{2\cdot1}=\dfrac{2\sqrt3}{2}=\sqrt3\\\\x_2=\dfrac{3\sqrt3+\sqrt3}{2\cdot1}=\dfrac{4\sqrt3}{2}=2\sqrt3[/tex]
Rozwiązanie odczytujemy z wykresu (patrz załącznik).
[tex]x\in\left<\sqrt3;\ 2\sqrt3\right >[/tex]